PING: A Group-to-Individual Distributed Meeting System - Rui, Yong; Rudolph, Eric; He, Li-wei; Malvar, Henrique S.; Cohen, Michael; Tashev, Ivan (Proceedings of International Conference Multimedia and Expo, 2006)
PC-based meeting-room-to-office (M2O) collaboration is an important but understudied area. Finding a solution to this problem is a current challenge in the multimedia research community. In this paper, we present the PING system which explicitly addresses a set of unique issues in the M2O scenario: 1) remote attendees tend to be ignored by the local participants; 2) remote attendees have inferior audio/video experience; 3) laptops brought to the meeting rooms are only loosely integrated to the meeting experience. Specifically, we combine low-cost hardware such as microphone arrays, remote person stand-in devices, and live whiteboard capture with the advances in audio-video processing, with an easy-to-use user interface. We discuss PING hardware design, software components, advanced features and system architecture.